2013
DOI: 10.3109/0886022x.2013.832313
|View full text |Cite
|
Sign up to set email alerts
|

Is IL-33 useful to detect early stage of renal failure?

Abstract: IL-33 is a proinflammatory cytokine that is a member of IL-1 family. Previously the effect of IL-33 on kidney injury is showed in animal models. In this study, we searched if we can use IL-33 to show the early stage of kidney injury in diabetic patients. Three groups are identified: 26 patients in Group 1: Healthy group, that do not have any chronic diseases and not taking any medication; 42 patients in Group 2: DM (diabetes mellitus) group without any known kidney disease and with normal kidney functions; 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…However, there was no difference when diabetic patients with or without nephropathy were compared. The results of this study suggest that IL-33 cannot be used as a marker of renal injury [48]. IL-6 is a proinflammatory cytokine and an important mediator of cell proliferation, endothelial cell permeability and increase in matrix production [55].…”
Section: Proinflammatory Cytokines and Dnmentioning
confidence: 84%
“…However, there was no difference when diabetic patients with or without nephropathy were compared. The results of this study suggest that IL-33 cannot be used as a marker of renal injury [48]. IL-6 is a proinflammatory cytokine and an important mediator of cell proliferation, endothelial cell permeability and increase in matrix production [55].…”
Section: Proinflammatory Cytokines and Dnmentioning
confidence: 84%
“…IL-33 serum levels of CKD patients were not significantly changed in the three groups but serum levels of sST2 strongly correlated with severity of the disease [58]. Another report by Caner et al demonstrated that IL-33 serum level was not better in early recognition of diabetic nephropathy [59]. The increase in IL-33 serum levels in diabetic nephropathy was not associated with kidney injury, whereas the increase might be a result of diabetes [59].…”
Section: Il-33 In Chronic Kidney Injurymentioning
confidence: 99%
“…Another report by Caner et al demonstrated that IL-33 serum level was not better in early recognition of diabetic nephropathy [59]. The increase in IL-33 serum levels in diabetic nephropathy was not associated with kidney injury, whereas the increase might be a result of diabetes [59]. Musolino et al reported that reduced IL-33 serum levels in multiple myeloma (MM) patients were associated with a more advanced stage of disease [60].…”
Section: Il-33 In Chronic Kidney Injurymentioning
confidence: 99%
See 2 more Smart Citations